Microhiological contamination (fecal coliforms) of soils due to the use of wastewater from the Arunta retention ponds, Tacna - Flores Cano, José Antonio (2025)
ABSTRACT The bacteriological contamination of the soils in the Arunta area was evaluated experimentally. For the research, the experimental variables considered were time (day) and the dosage of wastewater from the Arunta ponds (l/m2/day), which are the cause of bacteriological contamination. For the experimental research with the objective of modeling the speed of bacteriological contamination, the hexagonal design was used. Table 3 presents the experimental conditions of the variables and the results of the increase in soil contamination. The wastewater used for irrigation in Arunta, with a high contamination of 35,000,000 mg coliforms/l, dosed from 3.00 to 6.00 liters/m2/day and for a time varying from 33.61 to 54.39, increases the bacteriological contamination of the soil from 93.44% to 779.78%.